Productive and morphological features of sheep determined by biophysical methods. Issue 1 (May 2020) - Afanasyev, M A; Skorykh, L N; Kovalenko, D V; Omarov, A A
Abstract: The main trend in sheep breeding is a steady increase in the volume of mutton production which determines the increasing demand for meat and wool. The development and application of effective methods for increasing and improving meat productivity is relevant. Biophysical methods used in animal husbandry is of interest. One of the methods is the impact of low-intensity laser radiation. Biophysical methods used in animal husbandry can activate biological reserves and realize the genetic potential of productive qualities. At the same time, it is necessary to consider morphological features of sheep exposed to low-frequency infrared laser radiation. The article studies quantitative and qualitative indices of meat productivity, the degree of internal organs development, and the chemical composition of muscle tissues. Intergroup differences in young sheep exposed to low-frequency laser radiation were found. Positive changes in the degree of internal organs and systems development in animals exposed to low-intensity infrared laser radiation were identified. They indicate the intensity of metabolic processes in the body, the positive productivity dynamics.